The role of international organizations in perpetuating international humanitarian law: The United Nations as a model - Abdulghafoor Kareem Ali Ghafoor; Shivan Ahmed Abdulqadir Kofly (QALAAI ZANIST JOURNAL, 2019)
In this research the focus is on the foundation of philosophy which constitutes human international law. The role of international organizations in confirming and applying the law of human life is also discussed. Likewise, the responsibility of individuals along with the responsibility of jurisdictional systems of nations and the legal personalities of public international law are considered. In the present time, individuals as any other figures of public international law are bounded to responsibility. We have conceived that international society is ready to accept many cases in which individuals accept the jurisdiction authority. In many of those cases, they progress in that field and progress more in the future. We discuss about international jurisdiction court, Red Cross committee, doctors without borders, and several other organizations performing under the jurisdiction of international human law. The subject of this research which is international law of human rights and international jurisdiction law enables us to make up a new name for it, to say contemporary international law. The reason for taking up this name is that this new law has come to existence as a result of international jurisprudence either after the Second World War or even before the antiquity. In the contemporary era, this law has an institution for its application and execution, which in turn becomes a main criterion to try the international defendants and to punish them in order to protect human peace. The resulting conclusions are: 1. International Jurisdiction Law, 2. International Human Rights Law, 3. International Human Law and also International Jurisdiction Court. All of them become obstacles on the way of those who ignore human rights both in the time of war or the time of peace. The whole world attempts to protect social international security like the way they protect international security. All of the aforementioned discussions bring us the hope for realization of peace, security and welfare of the world. This can be done through working on expanding contemporary international law. In this study the main sources of international human law are discussed and the most significant international foundations and organizations which support it are disputed.